Between Phenomenology of Religion and Mysticism of Testimonial: Edith Stein versus Max Scheler and Martin Heidegger - Brejdak, Jaromir (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
This article begins with the presentation of three versions of phenomenology of religion shown as a maieutic turn in phenomenology: in case of Martin Heidegger,a Dasein as an enactment, in case of Max Scheler, a Person as an act. The second part of this work depicts Stein’s way towards God and tries to reconstruct her account of mysticalexperience based on her encounter with the thought of Saint John of the Cross. From a theoretical point of view, Edith Stein’s purpose seems to be limited, yet not in the merits of the case. Testimonial stays the only real way of experiencing God and reporting on His presence.